Bending behaviour of precast concrete slab with externally flanged hollow FRP tubes. (15th August 2021) - Al-Fakher, Usama; Manalo, Allan; Ferdous, Wahid; Aravinthan, Thiru; Zhuge, Yan; Bai, Yu; Edoo, Azam
Highlights: Introduced externally flanged hollow FRP tubes in concrete slab. Investigated bending behaviour with different tube spacing and shear span-to-depth ratio. Compared performance between epoxy coated and non-coated FRP tubes. Explained insight mechanisms using finite element modelling. FRP tube stabilised hollow core and improved structural performance. Abstract: Hollow-core precast concrete slabs are now being used in modular building construction to minimise the volume of concrete and to reduce their weight. However, the existence of voids in hollow-core concrete slabs makes the slab prone to premature failure. Recently, a composite reinforcing systems (CRS) has been developed to support the void in precast slabs. In this paper, the bending behaviour of a composite slab made from precast concrete with steel and CRS reinforcement was investigated. Four-point bending test was conducted for six precast slabs (solid, hollow without CRS, hollow with 2, 3 and 4 CRS, and hollow with 3 epoxy coated CRS) to comprehend the structural performance of this new precast concrete construction system. A non-linear finite element modelling was also conducted to gain an insight understanding the behaviour of the internal components of slab. The results showed that the CRS can stabilise the hollow core and act as additional reinforcement which enhances the load bearing capacity by 112% and the initial stiffness of the slabs by 24%.